Ethnic conflict in Buddhist societies in South and Southeast Asia : the politics behind religious rivalries - De Silva, K. M.; 25 Years in Retrospect: Buddhism, Ethnic Conflicts, and Religious Harmony in South and Southeast Asia (2014 : Kandy, Sri Lanka); De Silva, K. M.; International Centre for Ethnic Studies (2015)
Collection of select papers presented at a conference held in Kandy on 26-27 June 2014 on the theme of "25 Years in Retrospect: Buddhism, Ethnic Conflicts, and Religious Harmony in South and Southeast Asia."
Keywords: Buddhism -- Social aspects -- South Asia -- Congresses; Buddhism -- Social aspects -- Southeast Asia -- Congresses; Ethnicity -- Religious aspects -- Buddhism -- Congresses; Ethnic conflict -- South Asia -- Religious aspects -- Congresses; Ethnic conflict -- Southeast Asia -- Religious aspects -- Congresses; Buddhism and politics -- South Asia -- Congresses; Buddhism and politics -- Southeast Asia -- Congresses